Overseas Transaction Fees: Sending Money via Bitcoin vs. Banks - Sajter, Domagoj (Zagreb International Review of Economics & Business, 2022)
An important feature of every financial system throughout history is its capability to facilitate transfer of money in a secure and cost efficient manner. Cryptocurrencies as sources of innovative solutions – especially Bitcoin as their most prominent representative – have offered a completely new transmission system for a piece of information that can contain and carry value. There are many approaches to evaluate (un)successfulness of Bitcoin as money, and arguably one of the most important is to assess the fulfilment of its inventor’s original proposition: can it be used to send money directly and securely abroad, to international destinations, without fear of double-spending? Moreover, by removing institutions and their fees from the system hierarchy, can it be done for a lower price? The objective of creating Bitcoin network (among others) was to promote democratization of finance by enabling monetary transactions over the internet without unnecessary intermediaries inserting and charging multiple layers of fees. In decentralized, distributed blockchains such as Bitcoin and Ethereum subjects are incentivized to collectively maintain the public ledger (blockchain) by collecting block rewards (“coinbase”) and transaction fees. Block-chain maintenance is known as mining, and miners are compensated for their effort in the form of fees (and coinbase rewards) for verifying transactions. The objective of this paper is to examine and compare fees for transferring money internationally by means of Bit-coin network, in contrast to using traditional pathways, mostly banks, and in this manner to scrutinize the proof of concept and one of the cryptocurrency solutions to the issue of money transfer. By doing so we are attempting to provide answers to the questions of functionality and cost-effectiveness of an alternative financial system based on the blockchain technology. Transaction fees for international payments made by Bitcoin are compared by analysing a novel dataset obtained from World Bank and Croatian National Bank (CNB). CNB’s data is not publicly available, and was attained for this paper specifically. It contains 1.400 types of fees charged by the 23 banks operating in Croatia for the period of October 2018 to February 2022. Bank fees for international transactions were matched with Bitcoin fees in the same period, with the data taken from Blockchain.com online service. On average, to send 1,000 USD abroad by using Bitcoin network required approx. three times less in fees than by using banks in Croatia. The calculation structure of bank fees, also presented in the paper, required higher costs for sending lower amounts (in terms of percentage); when transferring 200 USD banks worldwide charged on average approx. 30 times more in fees than Bitcoin miners. Additionally, transaction fees for international remittances were analysed with quarterly data from World Bank. Comparative analysis of these and Bitcoin fees was made, and it is clear that (on average) sending money abroad via Bitcoin network bears significantly lower costs for the end user, especially when transferring lower amounts. Due to the non-normality of the distributions of the underlying variables, non-parametric tests were applied and the null hypothesis that transaction costs have identical medians was rejected. In conclusion, when needing to transfer money internationally users can obtain significantly lower costs by using decentralized technologies such as Bitcoin’s blockchain. This finding validates one of the key propositions of the distributed ledgers. Rather than focusing on wild daily Bitcoin price swings and its volatility, Bitcoin network functions as a cost-effective international payment system and proves itself as an alternative to traditional money transfer schemes.